2009
DOI: 10.1097/aog.0b013e318195888d
|View full text |Cite
|
Sign up to set email alerts
|

Complication and Reoperation Rates After Apical Vaginal Prolapse Surgical Repair

Abstract: The rate of complications requiring reoperation and the total reoperation rate was highest for vaginal mesh kits despite a lower reoperation rate for prolapse recurrence and shorter overall follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
2
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(177 citation statements)
references
References 31 publications
11
147
2
13
Order By: Relevance
“…The rate of mesh exposure in our study was 0.8 %, lower than those in published studies that reported a rate between 5.8 and 19 % [13,16,21]. The lower rate in the present study may be associated with short follow-up period and surgeon's experience on mesh application.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The rate of mesh exposure in our study was 0.8 %, lower than those in published studies that reported a rate between 5.8 and 19 % [13,16,21]. The lower rate in the present study may be associated with short follow-up period and surgeon's experience on mesh application.…”
Section: Discussioncontrasting
confidence: 56%
“…Diwadkar et al [13] in a meta-analysis of 24 studies including 3,425 patients and Gomelsky et al [16] in a review of 16 studies including 1,552 patients reported bladder injury as 0.7, 2.6 % and bowel injury as 0.3, 0.3 %, respectively. In the clinical studies, Kato et al [17] in 300 Patients and Caquant et al [18] in 684 patients reported bladder injury as 3.7, 0.7 % and rectal injury as 0.3, 0.3 % respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,17 Our study suggests the minimally invasive Capio results in similar levels of buttock pain than if the procedure is performed with the Miya hook.…”
Section: Resultsmentioning
confidence: 77%
“…Complete excision of the mesh is rarely indicated. Surgical procedures to partially or completely excise the mesh can be difficult; surgery may not always eliminate or reduce patient discomfort and can lead to further complications [150][151][152]. This is a particular problem of mesh-assisted surgical procedures, and it is therefore particularly important to provide the patient with detailed information on the risks involved.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%